2002
DOI: 10.4049/jimmunol.168.8.3833
|View full text |Cite
|
Sign up to set email alerts
|

The State of CD4+ T Cell Activation Is a Major Factor for Determining the Kinetics and Location of T Cell Responses to Oral Antigen

Abstract: Current models suggest that inductive immune responses to enteric Ag are initiated in Peyer’s patches (PP) and mesenteric lymph nodes (MLN) followed by migration of activated, memory-like CD4+ T cells to extralymphoid sites in the intestinal lamina propria (LP). The resultant immune system contains both naive and activated T cells. To examine the differential responses of naive and memory-like T cells to oral Ag, bone marrow chimeras (BMC) were generated. Irradiated BALB/c hosts were reconstituted with a mix o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 59 publications
1
4
0
Order By: Relevance
“…The results of the present study showed that high levels of anti‐ A. viscosus antibodies, predominantly the IgA isotype, were produced by PP cells taken from orally immunized mice. These results are in agreement with previous studies that oral immunization induced a mucosal immune response initiated in the PP in mice (6, 7). Furthermore, PP dendritic cells, which produce cytokines such as IL‐10, may preferentially help in the activation of Th2 cells, and hence in the generation of IgA + B cells (3, 10).…”
Section: Discussionsupporting
confidence: 94%
“…The results of the present study showed that high levels of anti‐ A. viscosus antibodies, predominantly the IgA isotype, were produced by PP cells taken from orally immunized mice. These results are in agreement with previous studies that oral immunization induced a mucosal immune response initiated in the PP in mice (6, 7). Furthermore, PP dendritic cells, which produce cytokines such as IL‐10, may preferentially help in the activation of Th2 cells, and hence in the generation of IgA + B cells (3, 10).…”
Section: Discussionsupporting
confidence: 94%
“…It has been reported that antigen‐specific T cells proliferate primarily in PPs and MLNs in response to oral antigen 22,23 . It seems reasonable to assume that providing costimulatory molecules on APCs would enhance such activation and/or proliferation of antigen‐specific T cells.…”
Section: Resultsmentioning
confidence: 99%
“…Upon activation following CD3ε ligation, murine CD8 + IELs produce interferon‐γ (IFN‐γ) more rapidly and to greater levels than CD8 + lymph node cells (15). Moreover, the activation state of CD4 + intestinal lamina propria cells also appears to reflect the nature of the intestinal response to oral antigens (20).…”
Section: Are Iels Activated T Cells?mentioning
confidence: 99%